The Impact of Achievement Motivation on Organizational Capabilities and Firm Performance in the Creative Industry Context - Tanjung, Immanuel Billy; Musa, Soebowo (UI Scholars Hub, 2021)
Research Aims: This paper aims to validate achievement motivation (AM) as a possible cause of the issues faced in the Indonesian creative industry context and establish a possible relationship between variables comprising organizational capabilities and organizational performance. Design/Methodology/Approach: This paper is a confirmatory study that uses a quantitative approach utilizing an online survey/questionnaire. The study examines 214 valid respondent survey answers from invited respondents from the Indonesian creative industry via email and social media platforms. Research Findings: This paper provides empirical validation of the hypotheses that AM is positively related with organizational capabilities and that those capabilities are positively related to firm performance (FP). This paper confirms past research findings regarding the relationships between the variables. Theoretical Contribution/Originality: This paper extends the research on AM to the organizational level and analyzes its relationships with organizational capabilities and FP in an integrated fashion. Managerial Implications in the South East Asian Context: This paper reveals AM as the possible true cause of the issues faced by the creative industry in Indonesia. Managers and government actors seeking to improve the industry should consider the AM of the workforce. Research Limitations & Implications: The limitations of this study are that the resulting analysis is limited to affirming past research on the variables and that this is a cross-sectional study with a specific research context; which implies that the results of this study only represent the condition at the specific point in time the research is conducted.